Eco-sustainable chromatographic method for the determination of favipiravir and nitazoxanide for COVID-19: application to human plasma - Amal B. Ahmed; Maha M. Abdelrahman; Fadwa H. Edrees (BMC Chemistry, 2025)
Abstract Coronavirus disease 2019 (COVID-19), an extremely contagious illness, has posed enormous challenges to healthcare systems around the world. Although the evidence on COVID-19 management is growing, antiviral medication is still the first line of treatment. Therefore, it is critical that effective, safe, and tolerable antivirals be available to treat early COVID-19 and stop its progression. Recently, favipiravir (FAV) has received FDA approval as safe and effective antiviral medication for COVID-19 management. Nitazoxanide (NTZ) also possesses antiviral and immunomodulating activities. Moreover, FAV and NTZ in combination are clinically used in COVID-19 treatment with reported safety, synergistic antiviral and immunomodulating effects. Despite the availability of various clinical studies on both FAV and NTZ, no existing analytical application for the simultaneous estimation of FAV and NTZ exists. As a result, the current work goal is to establish a green HPLC method for their analysis and implementation to human plasma. The developed method utilizes isocratic elution with 0.1% aqueous formic acid: ethanol (55:45, v/v) and dantrolene as internal standard. The bioanalytical validation parameters passed the FDA acceptance criteria. NEMI, eco scale, AGREE and ComplexGAPI approaches were used for qualitative and quantitative evaluation of the method’s greenness.